Higher slaughter weight affects broiler meat quality and bird welfare - NAGRE, GAJANAN K; KADAM, MUKUND M; BHAISARE, DARSHANA B; PATIL, ARCHANA R; GADEKAR, YOGESH P; RATHOD, KISHOR S (The Indian Journal of Animal Sciences, 2024)
An experiment was conducted to determine the influence of increasing broiler’s slaughter weight on, carcass characteristics, meat quality, sensory evaluation, immunity, and welfare. Commercial strain “Vencobb-430” chicks (n=280) were randomly distributed among eight groups consisting of 35 chicks in each. The experimental birds were fed on commercial maize soya-based basal diet. The broiler chicks were reared for up to 48 days and slaughtered at a different live body weight of 1.0-1.2, 1.5-1.7, 2.1-2.2, 2.5-2.7, 2.8-3.0 and 3.3-3.5 (i.e 24, 28, 34, 39, 42 and 48- day slaughter day). The results revealed that dressing and breast % were significantly (P2.1 kg, an increasing trend of gait score and breast cleanliness was observed at each stage of slaughter weight. Based on the results, the broiler birds reared up to 2.1 to 2.2 kg live body weight resulted in better welfare, immune status, and meat quality parameters.